Experience of piloting BPaLM/BPaL for DR-TB care at selected sites in Pakistan - M.A. Khan; A. Ismail; A. Ghafoor; N. Khan; N. Muzaffar; F. Zafar; A. Gupta; S. Foraida; S. Juneja; R. Fatima; A.W. Khan; S. Shahid; et al. (IJTLD Open)
BACKGROUND: Pakistan ranks fourth globally in terms of high drug-resistant TB (DR-TB) burden, with approximately one-third of cases resistant to fluoroquinolones. Bedaquiline, pretomanid, linezolid and moxifloxacin (BPaLM/BPaL) offers an opportunity for most DR-TB patients to benefit from a shorter, all-oral, well-tolerated and more effective treatment. METHODS: We conducted a retrospective cohort study to pilot the BPaLM/BPaL regimen at four selected sites in two provinces of Pakistan, i.e. Punjab and Khyber Pakhtunkhwa. Data were extracted and analysed using electronic medical records from the program. Descriptive statistics, survival analysis and binary logistic regression analysis were employed. RESULTS: A total of 116 patients took treatment between October 2022 and February 2023. The treatment success rate was 96%, with 3% deaths and <1% loss to follow-up. Patients typically completed treatment in 26.2–26.7 weeks for BPaLM and BPaL, respectively. No serious adverse events were observed. The most common side effects included QTcF prolongation (BPaLM: 55%, BPaL: 84%), haematological events (BPaLM: 32%, BPaL: 34%), and gastrointestinal problems (BPaLM: 36%, BPaL: 25%). CONCLUSION: The BPaLM/BPaL regimens for DR-TB are highly effective with minimal adverse events and feasible to implement in routine program circumstances.